2017
DOI: 10.1111/hex.12540
|View full text |Cite
|
Sign up to set email alerts
|

Involving Latina/o parents in patient‐centered outcomes research: Contributions to research study design, implementation and outcomes

Abstract: BackgroundComparative effectiveness research (CER) is supported by policymakers as a way to provide service providers and patients with evidence‐based information to make better health‐care decisions and ultimately improve services for patients. However, Latina/o patients are rarely involved as study advisors, and there is a lack of documentation on how their voices contribute to the research process when they are included as collaborators.ObjectivesThe purpose of this article was to contribute to the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Perez Jolles 2017 (Literature article) [43] For children's mental health efforts, a parents advisory group met every three months provided input on implementation research protocols, implementation decisions in the context of a study, interpreted findings, and suggested next steps.…”
Section: Examples and Intensity Levels Of Patient Engagement In Imple...mentioning
confidence: 99%
See 1 more Smart Citation
“…Perez Jolles 2017 (Literature article) [43] For children's mental health efforts, a parents advisory group met every three months provided input on implementation research protocols, implementation decisions in the context of a study, interpreted findings, and suggested next steps.…”
Section: Examples and Intensity Levels Of Patient Engagement In Imple...mentioning
confidence: 99%
“…• Meetings held only as often as needed, no more [56,58] • Limit to what is possible and do it well [43] • For lack of education, use multiple teaching methods to enhance knowledge (e.g., centralized trainer, online learning) [41] 4) Difficulty retaining patients over time in implementation effort Implementers found that if they were to engage patients representative of patients affected by a particular health condition or treatment (i.e., overcoming challenge #1), they were then faced with how to retain those patients because of limited capacity demanded by the very health condition or treatment under study. One mentioned experiencing "tremendous turnover. "…”
Section: Recurring Challenge 1: Lack Of Processes To Communicate Equi...mentioning
confidence: 99%
“…Research design and methods: Online portals to 14 ICMJE member journals were accessed to review how clearly data sharing policies are communicated to contributors and how this is balanced by journal's Open-access model [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . Results: Nine of 14 member journals communicated data sharing requirements on their websites.…”
Section: Abstractsmentioning
confidence: 99%
“…Numerous studies have found that multilingual and culturally responsive educational resources could build genetic health literacy and awareness, and subsequently improve participation in research [12][13][14][15]. Research has shown the profound impact of fostering trust-based relationships and bidirectional communication, emphasizing the inclusion of communities historically marginalized and exploited by biomedical research, notably Black and African American people who have been systematically excluded from the advances made with their contributions [16][17][18][19][20][21]. This inclusive approach has been shown to enhance interest and participation in research, particularly when intended beneficiaries are engaged throughout the development process [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%